Foreign bodies in the tracheobronchial tree. 12 years' experience. - Agostinho, M; Estevão, H M; Boavida, E; Pires, J; Pato, R; Isaac, J B; Coelho, A; Barroso, A (Acta Médica Portuguesa, 1997)
During a period of twelve years--January 1983 to December 1994, 371 children suspected of foreign body inhalation were admitted in Hospital Pediatric of Coimbra. The diagnosis was confirmed in 200 of them (54%), and this group was analysed. The incidence has increased until 1989 and stabilized in the last 5 years with a median of 18 cases/year. Two third of the children were boys and 84% were under three years old. A history of choking was obtained in 87% of the patients but only 39% of the cases had an early diagnosis (within 24 hours). The most frequent clinical findings were abnormal auscultation, sternal retraction, cough, wheezing and fever. Sixty percent of them were asymptomatic. The chest radiology findings were air trapping in 45%, consolidation in 21% and in 17% there were no abnormalities. Radiopaque foreign bodies were found in 9%. Organic bodies were the most frequent (74%) and among these, peanuts, lupines and beans. Food aspiration in one case took to cardiorespiratory arrest and in another with a late diagnosis bronchial stenosis needed a surgical treatment. Complications of foreign bodies extraction had no consequences.